EFFECT OF DIFFERENT LEVELS OF N-FERTILIZER ON THE GROWTH, DEVELOPMENT, ESSENTIAL OIL CONTENT AND COMPOSITIONS OF AGASTACHE FOENICULUM KUNTZE - Kaboudani, Maryam; Omidbaigi, Reza (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Anise Hyssop (Agastache foeniculum Kuntze.) is a half-hard perennial herb native to the plains of North America, which belongs to the Lamiaceae family. It has a pleasant anise-like aroma. To study the effect of nitrogen fertilizer on growth, development, essential oil content and compositions of Anise Hyssop, this research was carried out on randomized complete blocks design with three replications for every treatment. The effect of nitrogen fertilizer in 5 levels (0, 50, 100, 150 and 200 kg/ha) were studied. The essential oil was obtained by hydro distillation from the herb at full flowering stage. The results show that different levels of Nitrogen fertilizer had significant effect on the height of plant, essential oil content and compositions of Anise Hyssop. The results show that N-fertilizers had no significant effect on the number of branches per plant. The plants received 100 and 150 kg/ha nitrogen fertilizer had the highest essential oil content (2.88 and 2.83% respectively). Methyl chavicol was its main component (95.5%) and obtained from the plants were received 200 kg/ha nitrogen fertilizer. p-cymene (3.3%), caryophyllene (0.5%) and sabinene (0.1%) was the other components. It could be concluded that the suitable nitrogen fertilizer to obtain the maximum quantity and quality of active substances of Agastache foeniculum is recommended 150 kg/ha